SHAKING RED CAP-BLOOD COLLECTION TUBE WITHOUT ADDITIVE SUBSTANCES IS RECOMMENDED TO ACCELERATE THE BLOOD CLOTTING PROCESS - Gilang Nugraha; Rohayati Rohayati (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2019)
Many blood collection tube manufacturers do not recommend shaking the red tube. Shaking the red tube to avoid the intensity of the changed of blood that interacts with the glass surface of the tube will trigger the contact path in the coagulation cascade. Generally, the blood takes 30-60 minutes to clots at room temperature without shaking. The aim of this study was to determine the effectiveness of shaking the red-cap blood collection tube in producing serum volume. The method of this study was experimental As much as 5 mL of blood was taken and put into 3 tubes with a volume of 1mL each tube. The first and the second tube were shaken 8 times. The first tube was incubated for 10 minutes while the second tube was incubated for 25 minutes. Meanwhile, the third tube (as a control) was not shaken but was incubated for 40 minutes. The tube were centrifuged at 3000 g for 10 minutes. The serum volume was measured using micropipette and collected into Eppendorf tube. The results showed that there were a difference in the number of serums formed after tube shaking by time variation (P = 0.002), the results of the Post Hoc Test using Bonferroni test while showed that the second tube did not have a difference in serum volume with control (P = 0.751). It can be concluded that the red-cap blood collection tube, which was shaken 8 times and incubated for 25 minutes long could accelerate the coagulation process.